2018
DOI: 10.1021/acsbiomaterials.8b01046
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Titanium Surface via Click-Immobilization of Peptide and Its in Vitro/Vivo Activity

Abstract: The use of antimicrobial peptides (AMPs)-functionalized titanium implants is an efficient method for preventing bacterial infection. However, the attachment of AMPs to the surface of titanium implants remains a challenge. In this study, a “clickable” titanium surface was developed by using a silane coupling agent with an alkynyl group. The antimicrobial titanium implant was then constructed through the reaction between the “clickable” surface and azido-AMPs (PEG-HHC36:N3-PEG12-KRWWKWWRR) via click chemistry of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 61 publications
0
25
0
1
Order By: Relevance
“…For this purpose, multilayers coatings containing chlorhexidine were prepared on the surfaces of titanium particles used as a model for actual implant devices as the procedure employed to deposit the coating is not affected by the size or shape of the substrate. In this context, the nanoparticles prepared and studied in this work were used as other commonly employed material models such as rods [38][39][40], disks [41] or wafers [20]; thus we did not envisage depositing the coated nanoparticles onto the surface of devices [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, multilayers coatings containing chlorhexidine were prepared on the surfaces of titanium particles used as a model for actual implant devices as the procedure employed to deposit the coating is not affected by the size or shape of the substrate. In this context, the nanoparticles prepared and studied in this work were used as other commonly employed material models such as rods [38][39][40], disks [41] or wafers [20]; thus we did not envisage depositing the coated nanoparticles onto the surface of devices [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…In another study by Fang Z et al, polymer brushes with mono-and dual-peptide functionalized Ti rods implanted in a rabbit femur (bone) defect model exhibited excellent biocompatibility and antimicrobial activity [193]. Several other studies have reported in-vivo experiments [194][195][196][197][198] reinforcing the promise of using polymer-brush HDP-conjugate design to prepare functional biomaterial surfaces. In addition to their conjugation with standard polymer brushes, peptides with antimicrobial activity have also been integrated into or with other films/surfaces, such as protein-based films (i.e., self-assembled protein nanostructures) [199][200][201][202][203][204][205][206], silk surgical sutures [207,208], metal nanoparticles [209,210] and other solid interfaces, in order to provide biomaterials that can prevent and minimize the risks of bacterial infections.…”
Section: Surface Engineered Polymeric-brush-tethered Hdpsmentioning
confidence: 95%
“…Furthermore, the PEG‐HHC36 peptide on a Ti surface with a silane coupling agent, [ 194 ] GZ3.27 lipopeptide on glass silicon or Ti surfaces via a thioether bond, [ 195 ] inverso‐CysHHC10 peptide with a polyethylene glycol (PEG) network on poly(ethylene terephthalate) (PET), [ 196 ] IG‐25 on fluoropolymers and M2‐DA on stainless steel [ 197 ] are also reported as peptide AM coatings. Collectively, these coatings demonstrate a broad range of AM activities and modes of action.…”
Section: Perspective: Effective Antimicrobial Materials Not Yet Tested For Space Applicationsmentioning
confidence: 99%